A comparison of cotton and flocked swabs for vaginal self-sample collection - Viviano M; Willame A; Cohen M; Benski AC; Catarino R; Wuillemin C; Tran PL; Petignat P; Vassilakos P (Dove Medical Press, 2018)
Manuela Viviano,1 Alexia Willame,1 Marie Cohen,1 Anne-Caroline Benski,1 Rosa Catarino,1 Christine Wuillemin,1 Phuong Lien Tran,1 Patrick Petignat,1 Pierre Vassilakos2 1Division of Gynecology, Geneva University Hospitals, Geneva, Switzerland; 2Geneva Foundation for Medical Education and Research, Geneva, Switzerland Objective: Vaginal self-sampling for human papillomavirus (HPV) testing has recently been proposed to optimize cervical cancer screening coverage. The objective of this study was to compare the performance of self-taken samples using flocked and cotton swabs for HPV detection and cellular retrieval.Methods: We recruited women aged 21–65 years, referred to colposcopy at the Division of Gynecology of the Geneva University Hospitals between May and September 2016. Each participant collected 2 vaginal samples: 1 with a cotton swab and 1 with a flocked swab. A 1:1 randomization determined the order in which the 2 samples were taken. The swabs were introduced into a 20 mL PreservCyt® vial. Real-time polymerase chain reaction analysis using the Anyplex™ II HPV HR assay, cytofluorometric analysis and cytological cell counting were performed on each sample.Results: A total of 119 participants were recruited in the study. Their mean ± standard deviation age was 35.1±8.9 years. The HPV prevalence was 29.7% and 38.1% according to the cotton and flocked swab, respectively (p=0.006). The mean number of cells collected per milliliter according to cytofluorometry was 96,726.6 with the cotton swab and 425,544.3 with the flocked swab (p<0.001). The mean number of cells detected at cytological cell count was 13,130.42 using the cotton swab and 17,503.6 using the flocked swab (p<0.001). Conclusion: The flocked swab achieved a greater cellular retrieval and showed an improved performance in HPV detection. Further studies are needed to assess the usability and cost-effectiveness of the 2 self-sampling devices. Keywords: cervical neoplasia, cervical cytology, human papillomavirus, screening, flocked swab, HPV testing